Answer :

Let the series be S = (33 – 23) + (53 – 43) + (73 – 63) + ...


i) Generalizing the series in terms of i



Using a3 – b3 = (a – b)(a2 + ab + b2)






We know that and



S = 2n(n+1)(2n+1) + 3n(n+1) + n


S = 2n(2n2 + 2n + n + 1) + 3n2 + 3n + n


S = 4n3 + 6n2 + 2n + 3n2 + 4n


S = 4n3 + 9n2 + 6n


Hence sum upto n terms is 4n3 + 9n2 + 6n


ii) Sum of first 10 terms or upto 10 terms


To find sum upto 10 terms put n = 10 in S
S = 4(10)3 + 9(10)2 + 6(10)


S = 4000 + 900 + 60


S = 4960


Hence sum of series upto 10 terms is 4960


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

A person has 2 paRD Sharma - Mathematics

The sum of the seRD Sharma - Mathematics

How many terms ofRD Sharma - Mathematics

If <span lang="ENRD Sharma - Mathematics

Let anRD Sharma - Mathematics

Find the sum of 2RD Sharma - Mathematics

If <span lang="ENRS Aggarwal - Mathematics

Find the sum (41 RS Aggarwal - Mathematics

Find the sum (2 +RS Aggarwal - Mathematics

If<span lang="EN-RS Aggarwal - Mathematics